Side-Alternating Vibration Training Improves Muscle Performance in a Patient with Late-Onset Pompe Disease - Aneal Khan; Barbara Ramage; Ion Robu; Laura Benard (Case Reports in Medicine)
Side-alternating vibration training (SAVT) was used for 15 weeks in a patient with Late-onset Pompe disease who had never used enzyme replacement or chaperone therapy. Prior to the use of SAVT, the patient had experienced declining muscle performance and her 6-minute walk distance decreased from 210 to 155 metres in 6 months. After SAVT, her 6-minute walk distance increased 70% from 166 to 282 metres, muscle jumping power increased by 64% from 83 to 166 watts, isometric knee extensor strength increased 17% from 38 to 44 Nm, and she achieved a more normal pattern of ankle, knee, and joint kinematics and kinetics. Her functional ability measured through the Rotterdam 9-item score was unchanged at 19/36. There were no elevations in serum creatine kinase or lactate. This is the first report, to our knowledge, of a performance improvement in a patient with Pompe disease using SAVT.